Syed Abdul Malik and his novel-Agrhari Atmar Kahini: A Postcolonial study - Alom, Md. Jahangir (International Journal of Psychosocial Rehabilitation, 2019)
Syed Abdul Malik, an eminent novelist, Short Story writer, Poet, Playwright, Philosopher in Assamese literature was born at a small village of Golaghat district in Assam in North-East India. He had great attachment with various regional and national literary organizations throughout his lifetime. He was selected as secretary of ‘Assam Sahitya Sabha’ in 1977. He was awarded ‘Sahitya Akademi’ Award in 1972, ‘Padma Shree’ in 1984, ‘Padma Bhushan’ in 1992, from the Govt. of India, ‘Shankar Dev and Shahityachariya’ awards in 1999, other numerous awards from different social and academic bodies in the country. He has about seventy novels, more than one thousand Short Stories, ten Research Works, three Travelogues, twenty three Dramas, two Biographies, one Lyric, three Humorous writings, four Autobiographies, four Poems, five books on Children Literature and ten Translation works in his credit. He is one of the foremost literary figures in the North-East India who left behind such a huge literary contributions in Assamese literature. Akademi Award winner novel “Aghari Atmar Kahini” is a subjective novel depicting social disintegration, cultural degeneration and also their impact upon individual and society especially in the postcolonial era in our country particularly in Assam.